Strategi Siber Indonesia dalam Kerja Sama ASEAN untuk Menjaga Kedaulatan Digital - Muh. Fadlan Alfri Jamil; Agussalim Agussalim (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
In the era of rapid digital transformation, digital sovereignty has become a strategic issue for ASEAN countries, including Indonesia. Digital sovereignty encompasses a country's ability to manage data, technological infrastructure, and information systems independently without foreign intervention. This study aims to analyze Indonesia's strategies in strengthening digital sovereignty through regional cooperation within ASEAN. A descriptive qualitative approach is employed to illustrate the dynamics of Indonesia’s domestic and regional policies, with data obtained from literature studies, official government documents, and international publications related to cybersecurity. The findings indicate that Indonesia is actively developing national policies such as the Personal Data Protection Act (PDP Law), building national digital infrastructure, and launching strategic projects such as the SATRIA-1 Satellite. At the regional level, Indonesia plays an active role in forums such as the ASEAN Digital Ministers' Meeting (ADGMIN) and ASEAN-CERT, as well as initiating the establishment of the ASEAN Digital Resilience Task Force. However, significant challenges remain, including institutional fragmentation at the national level, digital infrastructure gaps, limited human resources, and varying political commitments among ASEAN member states. This study concludes that Indonesia's strategy must be accompanied by strengthened inter-agency coordination, capacity building of human resources, and harmonization of regional digital policies to create a secure, sovereign, and inclusive ASEAN digital ecosystem.